Nautiloid cephalopods – a review of their use and potential in biostratigraphy - Evans, Daniel H. (2014)
In terms of their use as biostratigraphical tools, nautiloid cephalopods are the poor relations of ammonoids. Nevertheless, in certain situations, they may provide useful biostratigraphical data, particularly where other biostratigraphically valuable taxa are not present; or in certain situations demonstrate a resolution as great as, or greater than ammonoids, trilobites, graptolites or conodonts. Nautiloid cephalopods are of especial value in palaeobiogeographical studies, but their use for this purpose may be hampered by the poor understanding of the stratigraphical ranges of individual taxa. The biostratigraphical value of nautiloid cephalopods is demonstrated here through a number of case studies of Ordovician taxa, combined with a review of their biostratigraphical use in Palaeozoic and Mesozoic successions. These both demonstrate the potential of this group and indicate great scope for further research.